The Role of Implicit Knowledge on Self- Marketing Success "A Prospective Study of The Views of a Sample of Registered Artists in The Kurdistanian Artists Guild / Dohuk Branch" - Ismael, Hadi Kh.; Salih, Shivan N. (Humanities Journal of University of Zakho, 2017)
The research aims to diagnose the role of implicit knowledge on self- marketing Success. Three dimensions of implicit knowledge were selected which were include in this study which were expertise, thinking, and skill. Six indicators of self-marketing success were also chosen which developing relations were, Self-confidence, the ability to convince. Take initiative and Being patient and determined. The research sample consisted of (80) artists whom are members of Kurdistan Artists Syndicate /Duhok those who work in the field of music, theatre, arts, and cinema. A questionnaire was use as essential means to collect data and by a serval statistic tools research hypothesis was tested. The most important research conclusions are there is significant correlation between implicit knowledge and self-marketing success; and implicit knowledge affect significantly in self-marketing success. The research presents a number of suggestions which include the necessary of acquiring implicit knowledge by artists, and inforce the level of their implicit knowledge by their continuous observation of the customers favorites and the businesses done by their competitors and the direction of market growth, and the importance of the cooperation between and academic enterprise to develop artists, self-marketing by making them participate in special training program.